2013
DOI: 10.1371/journal.pone.0055131
|View full text |Cite
|
Sign up to set email alerts
|

Accessory Gland as a Site for Prothoracicotropic Hormone Controlled Ecdysone Synthesis in Adult Male Insects

Abstract: Insect steroid hormones (ecdysteroids) are important for female reproduction in many insect species and are required for the initiation and coordination of vital developmental processes. Ecdysteroids are also important for adult male physiology and behavior, but their exact function and site of synthesis remains unclear, although previous studies suggest that the reproductive system may be their source. We have examined expression profiles of the ecdysteroidogenic Halloween genes, during development and in adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 74 publications
5
45
0
4
Order By: Relevance
“…S7A–C). On the other hand, ecdysone, another insect reproductive hormone (Belles and Piulachs, 2014; Hentze et al, 2013), had no effect on Or47b ORN sensitivity (not shown). Taken together, our loss- and gain-of-function experiments indicate that juvenile hormone is both necessary and sufficient for the elevated Or47b ORN sensitivity in males.…”
Section: Resultsmentioning
confidence: 94%
“…S7A–C). On the other hand, ecdysone, another insect reproductive hormone (Belles and Piulachs, 2014; Hentze et al, 2013), had no effect on Or47b ORN sensitivity (not shown). Taken together, our loss- and gain-of-function experiments indicate that juvenile hormone is both necessary and sufficient for the elevated Or47b ORN sensitivity in males.…”
Section: Resultsmentioning
confidence: 94%
“…In males, the steroid hormone is produced by and stored in the accessory glands (MAGs) to be further transferred to females during mating [26]. In both females and males, expression of the genes involved in the last steps of steroidogenesis is tightly correlated with ecdysteroid production [26] as described in several insect species [11][12], [27][31], as well as in crustaceans [32]. Taken together, all these results suggest that the timing of hormone production highly depends on transcriptional regulation of the enzymes involved in its biosynthesis.…”
Section: Introductionmentioning
confidence: 99%
“…This is not surprising considering that in adults, ecdysone biosynthesis genes are activated differently in the accessory glands and the ovaries [35]. The modular nature of gland specific regulation of hormonal production is probably very common.…”
Section: Discussionmentioning
confidence: 99%
“…*Results reported based on animals injected with dsRNA created using this primer set.a [63].b [59].c [61].d [71].e [40].f [35].…”
Section: Methodsmentioning
confidence: 99%